A ESPIRITUALIDADE NO AMBIENTE DE TRABALHO E SUA CONTRIBUIÇÃO PARA PERCEPÇÃO DE SUCESSO NA CARREIRA DO INDIVÍDUO - TENFEN, MARCELO FREITAS (2017)
For a lot of people work means the center of life and professional success brings a kind of satisfaction as well. According to this point of view an environment of day to day work linked with human feelings brings great benefits for both - workers and organizations. And it reflects for sure on businesses and cash-flow of these organizations. In fact, in companies like these people there become more creative what increases productivity as well. Therefore, spirituality is a complex phenomenon that cannot be ignored anymore by society and organizations all over the world. The present study has the aim to analyze the link between spirituality in the environment of work and the clear perception what really means to build a professional career and its success. In other words, it is very important to identify both dimensions - spirituality at one hand and professional success at the other hand, but having in view a life with purpose in a concrete perspective such as seeing it with an inner vision at the same time. The methodology that we used here deals with a quantitative approach, having a descriptive support by survey research by digital questions through networking tools (Twitter, Facebook, WhatsApp and e-mail). The target of this study was a mix worker with more than 5 years of professional experience, following the doctrine set by Venelli-Costa (2014) in order to evaluate what people really feel about success. The sample has 143 answers from São Paulo (Brasil). The analysis was done using a special software SPSS V. 20 (Statistical Package For the Social Sciences) - and to calculate the results and to be sure about the information brought by the statistics tests we used the multivariate of path structural equations of PLS - PM - Partial Last Square Path, with a tool named Software Smart PLS 3.0.M3. With the results discovered here, a really brand new one, we can assure this study brings to Brasil a great impact because in portuguese we could not find a single line about "spirituality" and "career" - from 2010/2016. The search was done in the newsletters published by CAPES. To conclude, spirituality in the environment of work causes a great impact in the real sense of a perception what success really means, let us say, in a wide dimension that a professional career also includes as well the truly purpose of a life full of meaning. We also must say that other researches also were done through multi group analysis in order to bring up to light other information among the target on focus.